A consciência dos adolescentes a respeito da sexualidade: uma visão junguiana - Storch, Carla Ribeiro do Lago (2012)
This research is a result of the master s degree dissertation in Clinical Psychology at PUC-SP Psychosomatic Center and Health Psychology, with theoretic reference in Analytical Psychology. The general objective of this research is the understanding of teenagers awareness about sexual behaviour and attitudes in the light of Jungian psychology. This study was done with 350 teenagers that attend a private school in the central region of the Capital of Sao Paulo - Brazil. The tools used to collect the data were: EAS-A Scale of Attitude and Scale of Reasons to Have and Not Have Sex, adapted, translated and validated by Storch (2012), to the brazilian population. The results showed that there are differences between the genders regarding attitudes, sexual behaviors and motivations to have sexual intercourse. The conclusion of the results shows that female teenagers present attitudes less sex utility, that is, a more emotional vision, when compared to male teenagers